A ficção entre duas épocas: tradução comentada do Essai sur les fictions e das Trois Nouvelles de Madame de Staël - Luiza Duarte Caetano (2018)
This Masters thesis proposes a commented translation, from French to Brazilian Portuguese, of the Essai sur les fictions [Essay on fiction] and the Trois Nouvelles [Three Novellas]respectively, Mirza ou Lettre dun voyageur [Mirza or letter from a traveler], Adélaïde et Théodore [Adelaide and Theodore] and Histoire de Pauline [Paulinas story]by Germaine de Staël. These were published for the first time in the Recueil de morceaux détachés [Collection of unrelated writings], in 1795. The objective of this paper is to investigate the importance of those worksbarely discussed and frequently referred to as the authors early worksin the understanding of de Staëls thought, as well as their contribution to her role in the passage from the belletristic paradigm to literature in its modern sense. In order to do that, this paper presents simultaneously the complete translation of the aforementioned works, as well as a series of critical and translational paratexts, such as a brief overview of their reception by past and present critics, explanatory, referential, interpretive and translation footnotes, and a dissertative comment on each novella and the essay. Supported by the contrast between the translation and its paratext, this thesis attempts to explore the hypothesis that, contrary to what the collections title suggests, the Essay on fiction and the Three Novellas are not unrelated. They would, instead, be bound by their reference to the Terror, still recent in 1795, and by the way in which Staëls thoughts on literatureboth in her theorization on fictions, and the practice represented by the novellasis not dissociated from her political and philosophical ideals, namely of equality, freedom and democracy.